Smoothing the Transition Points in Canadian Medical Education. (May 2018) - Busing, Nick; Rosenfield, Jay; Rungta, Kamal; Raegele, Matt; Warren, Andrew; Wright, Bruce; Walton, Mark; Oandasan, Ivy; Sanfilippo, Anthony; Saxena, Anurag
Abstract : In 2010, the Association of Faculties of Medicine of Canada, Collège des médecins du Québec, College of Family Physicians of Canada, and Royal College of Physicians and Surgeons of Canada launched the Future of Medical Education in Canada Postgraduate (FMEC PG) Project to examine postgraduate medical education (PGME) in Canada and make recommendations for improvement. One recommendation that emerged concerns the transitions learners experience across the undergraduate medical education–PGME–practice continuum. The FMEC PG, using a thorough process, developed projects to address these often-tumultuous transitions for the learner, aiming to provide support, tools, and standards for the learner's educational journey. With leadership by two senior academics and the Transitions Implementation Committee, three working groups helped implement these transitions projects, which addressed (1) the medical-school-to-residency transition, (2) career planning and the residency matching process, and (3) the residency-to-practice transition. Work products include the development of a learner education handover protocol and the establishment of pan-Canadian entrustable professional activities to be used nationally to help define expectations for new graduates entering residencies. A postmatch boot camp tool and a simulated night on-call tool were developed and are available to all medical schools. National standards are being promoted for career services counseling and best practices in residency selection. A practice management curriculum framework, mentorship resources, resiliency training for graduating residents, and the entry-level disciplines of residency are also being explored. Ultimately, with system-wide change and better integration of all players, transitions for Canada's learners will greatly improve.